2010
DOI: 10.5009/gnl.2010.4.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Rendezvous Technique for Biliary Stricture after Adult Right-Lobe Living-Donor Liver Transplantation with Duct-To-Duct Anastomosis

Abstract: Background/Aims: Replacement of a percutaneous transhepatic biliary drainage (PTBD) catheter with inside stents using endoscopic retrograde cholangiography is difficult in patients with angulated or twisted biliary anastomotic stricture after living donor liver transplantation (LDLT). We evaluated the usefulness and safety of the rendezvous technique for the management of biliary stricture after LDLT. Methods: Twenty patients with PTBD because of biliary stricture after LDLT with duct-to-duct anastomosis under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
(27 reference statements)
1
35
0
Order By: Relevance
“…After the guide wire has traversed the stricture via the PTBD route, endoscopic stent placement is relatively easy (Fig. 3) [78][79][80]. In cases with a completely obstructed BAS, in which identification of the anastomosis is difficult, we perform simultaneous cholangiogram via both an NBC and a PTBD tube to ensure the correct direction toward the anastomosis while attempting to pass a guide wire through the anastomosis via the PTBD route (Fig.…”
Section: Rendezvous Techniquementioning
confidence: 99%
“…After the guide wire has traversed the stricture via the PTBD route, endoscopic stent placement is relatively easy (Fig. 3) [78][79][80]. In cases with a completely obstructed BAS, in which identification of the anastomosis is difficult, we perform simultaneous cholangiogram via both an NBC and a PTBD tube to ensure the correct direction toward the anastomosis while attempting to pass a guide wire through the anastomosis via the PTBD route (Fig.…”
Section: Rendezvous Techniquementioning
confidence: 99%
“…However, stenting using ERCP in patients with angulated or twisted biliary strictures is difficult and sometimes fails. Our previous study showed that the rendezvous technique is a useful alternative method for successful placement of inside stents in these patients [13] . A few cases of biliary complication after liver transplantation have supported the usefulness of the rendezvous technique for biliary strictures and stones or biliary leakage from bile duct anastomosis [23][24][25] .…”
Section: Discussionmentioning
confidence: 97%
“…This combined technique increases the success rate of biliary tract cannulation and facilitates the diagnosis and treatment of biliary tract disorders [10][11][12] . We previously reported that the rendezvous technique allows for successful placement of inside stents in angulated or twisted biliary strictures after LDLT [13] . In the classic rendezvous technique, a guidewire is used for an endoscopic approach to the bile duct.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 This technique has been shown to have good results in patients with angulated or twisted biliary strictures for replacement of PTBD catheters with inside stents in biliary strictures after living donor liver transplantation. 57 The classical 'rendezvous' technique used percutaneously inserted guidewire for endoscopic approach to the bile tree while subsequently, multiple modifications of the technique have been suggested including Kumpe catheter instead of guidewire with promising results. 58 Surgery remains the last resort to salvage the graft when multiple endoscopic and percutaneous attempts fail.…”
Section: Percutaneous Biliary Intervention In Post Liver Transplant Rmentioning
confidence: 99%